Pneumocystis jirovecii colonization in Chronic Obstructive Pulmonary Disease (COPD) - Sadegh Khodavaisy; Esmaeil Mortaz; Faezeh Mohammadi; Masoud Aliyali; Hamed Fakhim; Hamid Badali (Mazandaran University of Medical Sciences, 2015)
Chronic obstructive pulmonary disease (COPD) is associated with a chronic inflammatory response in airways and lung parenchyma that results in significant morbidity and mortality worldwide. Cigarette smoking considered as an important risk factor plays a role in pathogenesis of disease. Pneumocystis jirovecii is an atypical opportunistic fungus that causes pneumonia in immunosuppressed host, although the low levels of its DNA in patients without signs and symptoms of pneumonia, which likely represents colonization. The increased prevalence of P. jirovecii colonization in COPD patients has led to an interest in understanding its role in the disease. P. jirovecii colonization in these patients could represent a problem for public health since colonized patients could act as a major reservoir and source of infection for susceptible subjects. Using sensitive molecular techniques, low levels of P. jirovecii DNA have been detected in the respiratory tract of certain individuals. It is necessary to elucidate the role of P. jirovecii colonization in the natural history of COPD patients in order to improve the clinical management of this disease. In the current review paper, we discuss P. jirovecii colonization in COPD patients.